2022
DOI: 10.5435/jaaos-d-22-00456
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heart Disease History on Safety of Telemedicine Cardiac Clearance Appointments

Abstract: Purpose:The objective of this study was to compare complication, readmission, mortality, and cancellation rates between patients who had either an in-person or telemedicine preoperative cardiac clearance visit before spine surgery.Methods:A retrospective review was conducted on patients who underwent a spine procedure at a single tertiary academic center from February 1, 2020, to June 30, 2021. Cancellations, inpatient complications, 90-day readmissions, and inpatient and 90-day mortality rates were compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…On assessing whether the episode of care was associated with a surplus or deficit, we similarly identified that a history of heart disease and venous thromboembolic events were more likely to predict a loss. Given that cardiovascular conditions, including heart failure and heart disease, have been associated with increased healthcare costs because of greater postoperative complications and readmissions after lumbar spine surgery, 20-22 preoperative cardiac evaluation and medical optimization may reduce resource utilization after lumbar decompression and lumbar fusion care episodes. Interestingly, increasing age and diagnoses of chronic lung disease and arrhythmia were associated with a greater surplus.…”
Section: Discussionmentioning
confidence: 99%
“…On assessing whether the episode of care was associated with a surplus or deficit, we similarly identified that a history of heart disease and venous thromboembolic events were more likely to predict a loss. Given that cardiovascular conditions, including heart failure and heart disease, have been associated with increased healthcare costs because of greater postoperative complications and readmissions after lumbar spine surgery, 20-22 preoperative cardiac evaluation and medical optimization may reduce resource utilization after lumbar decompression and lumbar fusion care episodes. Interestingly, increasing age and diagnoses of chronic lung disease and arrhythmia were associated with a greater surplus.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 7 mostly small observational studies 16,27,35,39,[56][57][58][59] . Studies reported a variety of adverse events across 4 of the clinical areas (Fig.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…3C, Supplementary Table 8 -Bottom Tier, and Supplementary Fig. 1C) 28,31,43,45,52,[59][60][61][62][63][64][65][66][67][68] . For general medical care among adults (N = 2 studies) telehealth resulted in a higher rate of missed visits.…”
Section: Process Outcomesmentioning
confidence: 99%